Longitudinal Reduction in Diversity of Maternal Gut Microbiota During Pregnancy Is Observed in Multiple Low-Resource Settings: Results From the Women First Trial - Tang, Minghua; Weaver, Nicholas E.; Frank, Daniel N.; Ir, Diana; Robertson, Charles E.; Kemp, Jennifer F.; Westcott, Jamie; Shankar, Kartik; Garces, Ana L.; Figueroa, Lester; Tshefu, Antoinette K.; Lokangaka, Adrien L.; et al. (Frontiers in Microbiology, 2022)
Objective: Characterize the gut microbiota changes during pregnancy and determine the effects of nutritional intervention on gut microbiota in women from sub-Saharan Africa (the Democratic Republic of the Congo, DRC), South Asia (India, Pakistan) and Central America (Guatemala). Methods: Pregnant women in the Women First (WF) preconception maternal nutrition trial were included in this analysis. Participants were randomized to receive a lipid-based micronutrient supplement either ≥ 3 months before pregnancy (Arm1); started the same intervention late in the first trimester (Arm 2); or received no nutrition supplements besides those self-administered or prescribed through local health services (Arm 3). Stool and blood samples were collected during 1st and 3rd trimesters. Findings presented here include fecal 16S rRNA gene-based profiling and systemic and intestinal inflammatory biomarkers, including alpha (1)-acid glycoprotein (AGP), C-reactive protein (CRP), fecal myeloperoxidase (MPO) and calprotectin. Results: Stool samples were collected from 640 women (DRC n=157; India n=102; Guatemala n=276; Pakistan n=105). Gut microbial community structure did not differ by intervention arm but changed significantly during pregnancy. Richness, a measure of alpha-diversity, decreased over pregnancy. Community composition (beta-diversity) also showed significant change from 1st to 3rd trimester in all four sites. Of the top 10 most abundant genera, unclassified Lachnospiraceae significantly decreased in Guatemala and unclassified Ruminococcaceae significantly decreased in Guatemala and DRC. The overall community structure change at the genus level was a decrease in the abundances of certain genera with low heterogeneity among the four sites. Intervention arms were not significantly associated with inflammatory biomarkers at 12 or 34 weeks. AGP significantly decreased from 12 to 34 weeks of pregnancy whereas CRP, MPO and calprotectin did not significantly change over time. None of these biomarkers were significantly associated with gut microbiota diversity. Conclusion: The longitudinal reduction of individual genera (both commensals and potential pathogens) and of alpha-diversity among all sites was consistent and suggested that the effect of pregnancy on the maternal microbiota overrides other influencing factors such as nutrition intervention, geographical location, diet, race, and other demographical variables.